Strategies for Maintaining Friendship in Dementia. Issue 3 (6th September 2022) - Genoe, M. Rebecca; Fortune, Darla; Whyte, Colleen
Abstract: Although friendship is vital in later life, particularly amongst people who are living with dementia, little is known about how friendships are sustained following a diagnosis. Some research suggests that, because of dementia-related stigma, friendships dissolve following diagnosis; however, other researchers have shown that friendships can persist in dementia. The purpose of this article is to explore strategies that people with dementia and their friends (i.e., those who have been friends for at least 2 years) utilize to sustain their friendships. Following a constructivist approach, we interviewed people living with dementia, friends, and family members to better understand how friendships are maintained after a diagnosis of dementia. Data were analyzed using thematic analysis. An overarching theme, adapting to change, was generated. Participants adapted in several ways, including: (1) prioritizing friendship, (2) shifting ways of thinking about our friend/ship, and (3) addressing changes through practical strategies. These strategies helped maintain mutually beneficial, reciprocal friendships that were able to withstand changes that accompany a diagnosis of dementia.